Efektivitas Psikoedukasi Wawasan Kebangsaan untuk Menurunkan Kecenderungan Radikalisme pada Mahasiswa - Eko April Ariyanto; Sayidah Aulia Ul Haque; Achmad Rizal Syafii (Faculty of Psychology, Universitas Semarang, 2019)
This research is motivated by the growing understanding of radicalism in Indonesia, including among the young generation of Indonesia. The younger generation should be the hope of the nation to continue the struggle of the predecessors to advance Indonesia, but if the young generation has been exposed to radicalism, it is necessary to provide an intervention in this case in the form of psychoeducation. The purpose of this study was to determine the effect of